Are there economies of scale in stock exchange activities? - Markku Malkamäki (Bank of Finland, 1999)
This is the first paper that examines economies of scale in stock exchanges.The data employed in the study include cost and output statistics for 37 stock exchanges in four continents around the world for the year 1997.I estimate two traditional cost functions and find that ray (overall) scale economies exist only in the very large stock exchanges but that there are significant scale economies with respect to one of the outputs, ie the processing of trades.On the other hand, there are not equally clear scale advantages related to activities involving company-specific information.There are thus opposing forces, some tending to increase standardization and scale and others favouring the continuization of more localized facilities.The outcome of increasing competition may be not be the amalgamation of exchanges but instead the centralization of certain functions, eg the trading function, and continued realization of others on a decentralized basis.There is nonetheless an obvious incentive for closer and deeper cooperation between European stock exchanges.
URN:NBN:fi:bof-20140807128
Keywords: 330